The emerging markets century: how a new breed of world-class companies iss overtaking the world - Van Agtmael, Antoine (New York: Free Press, 2007)
Contents: Globalization has no borders. The new breed: twenty-five world-class emerging multinationals. turning threats into opportunities. An investor's resource